The effect of adding rice husk ash (RHA) and calcined shell powder (CSP) on the properties of cement mortar - J.X. Zhang; Y.T. Guo; S.Y. Zhuang; H.Q. Lou; Y. Li (Case Studies in Construction Materials)
To enhance sustainability in the construction industry, incorporating rice husk ash (RHA) as a partial cement replacement is widely encouraged. Additionally, bio-shells, rich in CaCO₃, pose environmental challenges when improperly discarded, leading to pollution and negative impacts on surrounding communities. This study integrates the beneficial properties of these two waste materials for use in construction. While the effects of RHA on cementitious materials have been extensively studied, limited research has examined the combined influence of RHA and calcined shell powder (CSP) as a partial cement replacement. To explore their potential, RHA and CSP were blended in varying proportions to produce RHA-CSP cement mortar. Experimental results demonstrated that the R15S10 mix achieved the highest mechanical performance by optimizing the balance between pozzolanic reactivity and the filler effect. As hydration progressed, the pozzolanic reaction intensified under high pH conditions, increasing the C-S-H dehydration peak while reducing the CH decomposition peak. Additionally, the incorporation of CSP and RHA refined the pore structure and decreased overall porosity, enhancing mortar compactness. By utilizing these waste materials to create an optimized mix, this study supports the sustainable application of discarded shells and rice husks in construction.